KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 29 KABUPATEN SIJUNJUNG - Putra, Toni Eka; Laila, Aruna; Ramadansyah, Ramadansyah (Pendidikan Bahasa Indonesia, 2013)
The background of this research was the problem that the students faced in the VIII grade studendsâ of SMP N 29 Kabupaten Sijunjung in writing the news was not better in aplplying 5W+1H. More over 5W+1H items in the news was very important items. The good news should be able to answer the items 5W+1H. This research has the purpose to describe the ability of writing news text at the VIII grade of SMP N 29 Kabupaten Sijunjung. The kind of this research used was qualitative research with used descriptif method. In this research the all population to be sample because the population less from 100. The date of this research was used news text that the students wrote at the VIII grade studentsâ of SMP N 29 Kabupaten Sijunjung that it got though test in essay from.The result of this research showed that the ability of writing news text students at the grade VIII studentsâ of SMP N 29 Kabupaten Sijunjung was good (B) with the mean score 77,18%. Next, the ability of students writing news text at the VIII grade studentsâ of SMP N 29 Kabupaten Sijunjung seen from the itemsâ (1) what/apa was very good (BS), with the mean score students 89,33%, (2) who/siapa was enough (C), with the mean score students 64%, (3) where/dimana was good (B), with the mean score students 78,22%, (4) when/kapan was very good (BS), with the mean score students 87,11%, (5) why/kenapa was enough (C), with mean score students 69,78%, and (6) how/bagaimana was more than enough (LdC), with the mean score students 74,67.